Analisis Kesalahan Berbahasa pada Teks Berita dalam Platform Digital Kompas Edisi Desember 2023 sebagai Alternatif Membaca Kritis Siswa Kelas IX SMP - Andini Bella Pertiwi; Dita Idmania; Octa Surya Pradana; Rizkamalia Ciptarini Mega Gustami; Salsabila Zain Syafa; Asep Purwo Yudi Utomo; Ahmad Ripai (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to identify and explain errors in the structure, function, and role of language in news texts on digital platforms. This research is useful to know how to classify sentences and improve sentence structuring, and then the results of the research can be used in Indonesian language learning in grade IX junior high school. The method used is the descriptive qualitative method. The method analyzes language errors, such as analyzing keywords, grammatical error analysis, and semantic error analysis. The data used in the analysis uses descriptive methods so that it can be done in this study describes the data in the form of several sentences in the Kompas digital news text that contains words that are less understandable to junior high school students in grade IX, it can affect students in critical reading analyzing these errors, this article also provides improvements. These errors need to be overcome so that in the future the same language errors will not be repeated. Efforts that can be made to overcome Indonesian language errors at the level of spelling are to improve mastery of Indonesian language rules.